PENGARUH MEDIA AUDIO TERHADAP KEMAMPUAN MENYIMAK CERITA RAKYAT PADA SISWA KELAS V SD NEGERI 2 TIAKUR - Unawekla, Ansalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on classroom observations conducted in Grade V of SD Negeri 2 Tiakur, it was found that Indonesian language learning, particularly in listening to folklore, was not yet optimal. The comprehension of the material delivered by the teacher had not been fully absorbed by the students, resulting in a generally low level of student engagement during the learning process. This condition was influenced by the limited and suboptimal use of instructional media, which failed to stimulate students’ motivation to learn. This study employed a quantitative research design with an experimental approach. The purpose of the study was to examine the effect of audio media on students’ ability to listen to folklore. The research design used was a control group pretest–posttest design involving an experimental group and a control group. Data were analyzed using descriptive and inferential statistical techniques. The results of the data analysis indicated that the use of audio-based instructional media had an effect on students’ listening skills in Indonesian language learning for Grade V students at SD Negeri 2 Tiakur. This finding was supported by the results of the Paired-Samples T Test, which showed a Sig. (2-tailed) value of 0.076 (> 0.05), indicating an effect of audio media on listening skills. Furthermore, the average learning outcomes of students in the experimental group increased from 54 to 80.2, while the control group, which applied conventional teaching methods, showed a smaller increase from 49.6 to 65.